Como os agricultores familiares dos municípios de Viçosa e Coimbra em Minas Gerais avaliam o uso do milho transgênico - Silveira, Janine Fernanda da (2018)
The aim of this study was to analyze how the family farmers of Viçosa and Coimbra evaluate the use of transgenic, specifically the maize seed in agriculture, starting from the importance of the transgenic because it is a technology that has a lot of care in relation to its use, and permeated with great controversy. In this sense, it was understood how the family farmer with various specificities and own culture would be dealing with this innovation in agriculture. For this, the research was based on qualitative methods, through the development of individual interviews and observations. Seeking success in this purpose, it was initially the contact with the extension technicians of EMATER of Viçosa and Coimbra for the identification of the family farmers who use transgenic maize, from this, the universe and sample of the research in the municipalities were defined, which were 12 family farmers from Viçosa organized in the known ¨pública do leite¨, and 12 family farmers from Coimbra, both farmers use corn for silage. A regional coordinator and two agricultural extension workers composed the sample of extension technicians of EMATER. The results were analyzed and interpreted according to the information available in the literature, based on the theoretical assumptions that guided this work, in order to answer the aims of the same. Finally, conclusions were drawn, it was noted that family farmers are using transgenic maize for the desire to increase production and facilitate management using the herbicide, dispensing to weeding, but that sales representatives of agricultural companies operating in the region influence the use. They are planting transgenic maize incorrectly, without making the area of refuge, so in the future they will have problems with insect resistance. Most people think transgenic maize does not cause contamination, problems for the health or the environment. It is analyzed that this study allowed knowing the idea that the familiar farmers has on the transgenic maize, however, it is mediated of external influences that encourage them in the use. It is hoped that this research can serve as a basis for further development of other studies, by explaining a present reality.